Draft Annual Plan 2003-2004 Government of Jharkhand - Planning Commission (Planning Commission, 2003)
Jharkhand, India's youngest and 28th State came into existence on 15th November 2000. This area was one of the most neglected part of the erstwhile Bihar. the per capita investment on development was negligible in comparison to the revenue generated by the area. the State Government is committed to accelerate the pace of the development with a view to transform Jharkhand into a modern State. The State is divided into 22 districts comprising of 4 divisions covering an area of 79,714 sq. km. the cultivable area is 38 lakh Ha and the present net sown area is 18.04 Ha. the net irrigated area is only 1.57 lakh Ha., which is 8% of the total sown area.
Planning and Development Department Government of Jharkhand